Design of mobile band subsurface antenna for drainage infrastructure monitoring. Issue 13 (30th July 2019) - See, Chan H.; Kosha, Jamal; Mshwat, Widad A.; Abd‐Alhameed, Raed A.; Ong, Felicia L.C.; McEwan, Neil J.; Excell, Peter S.
Abstract : This study presents an underground subsurface wireless sensor for drainage infrastructure water level monitoring. It operates from 800 to 2170 MHz to cover the required GSM850/900, GSM1800/1900 and Universal Mobile Telecommunications System (UMTS) bands. The system consists of a wideband antenna, transceiver, data acquisition unit and an ultrasonic sensor. The proposed antenna is a three‐dimensional inverted double F antenna and has an envelope size of 90 × 63.5 × 32 mm 3, which is acceptably small for a cramped subsurface passageway environment. The antenna design was developed using software simulation to optimise its key parameters of return loss and radiation pattern, these were evaluated both in free space and in the partially underground environment. The design developed was then realised in hardware and tested in a representative subsurface location: a utility manhole chamber. It was found that the location of the antenna in the chamber had a significant effect on its performance, but a location that was acceptable for operational purposes was found by experiment. The overall system, including a transceiver, was demonstrated to operate satisfactorily for utility monitoring purposes, including acceptable levels of path loss for communication with mobile communication base stations.